(untitled) (African Disability Rights Yearbook, 2021)
Using a qualitative methodological approach, the study examined the situation of persons with disabilities in Liberia. In addition, it examined the efforts of the Liberian government in ensuring the protection of their rights within both the African and Global Human Rights frameworks to ascertain the extent of state effort towards protecting, fulfilling, and promoting the rights of persons with disability. The study engages with relevant stakeholders to ascertain the extent of implementation of state obligations and the role of institutions and policies in ensuring that persons with disabilities are not subjected to violations. Conclusively, the study finds that despite the efforts of government and collaboration with Civil Society Organisations and other agencies, there is yet so much need for promotional activities to ensure the realisation of the rights of persons with disabilities in Liberia.